Device-based interventions that seek to restore bilateral and binaural hearing in adults with single-sided deafness: a conceptual analysis - Katiri, Roulla; Peters, Jeroen P. M.; Fackrell, Kathryn; Hoare, Derek J. (Frontiers in Audiology and Otology, 2023)
Single-sided deafness (SSD) is defined by severe-to-profound sensorineural hearing loss in one ear only. This article outlines the etiologies and associated functional, psychological, social, and other consequences of SSD in adulthood. The available hearing aids and auditory implants for SSD are described, alongside an overview of the methods adopted by clinicians and researchers to define and measure their benefits and harms. Current concepts and issues to consider in the field of rerouting and restoring device-based interventions are explored. A contemporary overview of the current challenges in outcome measurement of all available interventions in the field is also provided, and cost effectiveness of SSD interventions is discussed briefly. This article therefore proves a comprehensive summary of the current knowledge on interventions and outcome measurement for SSD for those interested or actively working in the field, and recommendations for future trials. These include recommendations on the timescale of measurements, long-term benefits (or harms), cost utility, and the use of the internationally agreed core outcome domain set for all future clinical trials of device-based interventions for SSD.